Use of Graphs and Tables in Estate Planning - Ralph R. Neuhoff (Washington University Law Quarterly, 1958)
There are two kinds of transfer taxes, liability for which may be incurred in passing property from one generation to another: estate taxes and gift taxes. Although each operates in the same area, the impact of the gift taxes is very much less than that of estate taxes, a fact not fully appreciated by many people. The advantage gained by incurring gift taxes through gifts designed to obviate the imposition of estate taxes is so great that, as a practical matter, many or, in fact, most tax-payers of substantial means should rely as heavily as possible upon making gifts, if their object is to reduce the total impact of transfer taxes upon their estates. The questions to be resolved are just how far one should go and how one decides how much to give away in order to benefit from the disparity of the tax treatment of gifts as against transfers at death. This Article deals with the application of tables and graphs in finding the solution to the problem of determining the advisable size of an inter vivos gift for the purpose of taking advantage of the tax saving which is available.
Keywords: Estate planning